2017
DOI: 10.1111/medu.13272
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the effectiveness of flipped classrooms in medical education

Abstract: There has been a recent increase of research rigor and variety in measures of effectiveness in studies on the FC in medical education. The FC is a promising teaching approach to increase learners' motivation and engagement. More solid evidence on its effect on changes in knowledge and skills are warranted. Further studies should also examine the long-term effects of FCs with regard to knowledge retention and transfer of knowledge to professional practice and patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
536
2
31

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 566 publications
(601 citation statements)
references
References 35 publications
32
536
2
31
Order By: Relevance
“…Recently, the flipped classroom approach has received much attention in medical education [17]. The flipped classroom requires students to obtain background knowledge through homework prior to a face-to face class meeting, and reserves precious in-class time for applying knowledge to solve real clinical problems through discussion facilitated by faculty [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the flipped classroom approach has received much attention in medical education [17]. The flipped classroom requires students to obtain background knowledge through homework prior to a face-to face class meeting, and reserves precious in-class time for applying knowledge to solve real clinical problems through discussion facilitated by faculty [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…A large body of recent literature has reported the application of flipped classroom in health sciences education, including nursing, pharmacology, physiology, radiology, epidemiology, and stomatology [17,2230]. More recently, the flipped classroom approach has been extended to medical clerkship teaching with encouraging results, such as clerkships in emergency medicine and surgery [22,3133].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent scoping review of the literature across higher education noted that much of the emerging evidence of improved academic performance is indirectly related to the FC, with a paucity of conclusive evidence being put forward to support its utility (O'Flaherty and Phillips, 2015). Furthermore, and specifically in relation to medical education, a systematic review found that despite the positive perceptions of FCs, the effects on changes in knowledge and skills were less conclusive and suggested a lack of evidence on its effectiveness (Chen et al, 2017). However, two recent research articles have shown the potential of a FC in relation to histology and gross anatomy teaching.…”
Section: Is the Fc Always Appropriate?mentioning
confidence: 99%
“…Furthermore, a 2015 scoping review on flipped classrooms, O’Flaherty and Phillips’ results indicate that although there was indirect evidence of improved academic performance and student and faculty satisfaction with the flipped classrooms, there was a paucity of conclusive evidence that the flipped classroom format contributed to building lifelong learning and skills [11]. A more recent 2017 systematic review on the effectiveness of flipped classrooms by Chen et al confirm that while there were generally positive perceptions of the flipped classroom approach, the effect of flipped classrooms on changes in knowledge and skills were less conclusive in promoting knowledge acquisition above and beyond the more ‘traditional’ learning methods [12]. The review of evidence highlights the variations in teaching outcomes is probably dependent on many factors other than just the teaching format.…”
Section: The Classroom Networkmentioning
confidence: 99%